VD_FINDINFO HC / 2017 / 575 vom 5. Mai 2017 - VD Tribunal cantonal (2017)
LITISPENDANCE, ACTION EN DIVORCE, DROIT INTERNATIONAL PRIVÉ, SUSPENSION DE LA PROCÉDURE | 9 LDIP, 106 al. 1 CPC (CH), 107 al. 1 let. c CPC (CH), 126 al. 1 CPC (CH)